Mucocele of the appendix: a rare case report - P. B., Sudarshan; S., Reshma (International Surgery Journal, 2017)
Appendiceal mucocele is a rare disease. Sometimes it is discovered accidentally and sometimes it resembles acute appendicitis. Correct diagnosis before surgery is important for the selection of adequate surgical treatment to avoid intraoperative and postoperative complications. Ultrasonography, and particularly computed tomography, should be used extensively for this purpose. If mucocele is treated incorrectly, pseudomyxoma peritonei may develop. We present a case of 22 year old man who was admitted to the emergency department with the signs of acute appendicitis. Emergency open appendectomy was performed. At the time of surgery, a cystic mass was found at the tip of the inflammed appendix. No free fluid was found in the peritoneal cavity. Diagnosis of Mucocele of appendix was suspected. Appendectomy was done and specimen sent for histopathological examination. No lymphadenopathy. Histopathologic diagnosis was subacute appendicitis, mucocele of appendix with simple mucous cyst. Patient is on regular follow-up.